Proof of concept of a new plasma complement Factor H from waste plasma fraction - Mori, Filippo; Pascali, Giancarlo; Berra, Silvia; Lazzarotti, Alessandra; Panetta, Daniele; Rocchiccioli, Silvia; Ceccherini, Elisa; Norelli, Francesco; Morlando, Antonio; Donadelli, Roberta; Clivio, Alberto; Farina, Claudio; et al. (Frontiers in Immunology, 2024)
Complement factor H (FH) is a major regulator of the complement alternative pathway, its mutations predispose to an uncontrolled activation in the kidney and on blood cells and to secondary C3 deficiency. Plasma exchange has been used to correct for FH deficiency and although the therapeutic potential of purified FH has been suggested by in vivo experiments in animal models, a clinical approved FH concentrate is not yet available.We aimed to develop a purification process of FH from a waste fraction rather than whole plasma allowing a more efficient and ethical use of blood and plasma donations. Methods:Waste fractions from industrial plasma fractionation (pooled human plasma) were analyzed for FH content by ELISA. FH was purified from unused fraction III and its decay acceleration, cofactor, and C3 binding capacity were characterized in vitro. Biodistribution was assessed by high-resolution dynamic PET imaging. Finally, the efficacy of the purified FH preparation was tested in the mouse model of C3 glomerulopathy (Cfh-/-mice). Results: Our purification method resulted in a high yield of highly purified (92,07%), pathogen-safe FH.FH concentrate is intact and fully functional as demonstrated by in vitro functional assays.The biodistribution revealed lower renal and liver clearance of human FH in Cfh-/-mice than in wt mice. Treatment of Cfh-/-mice documented its efficacy in limiting C3 activation and promoting the clearance of C3 glomerular deposits.We developed an efficient and economical system for purifying intact and functional FH, starting from waste material of industrial plasma fractionation. The FH concentrate could therefore constitute possible treatments options of patients with C3 glomerulopathy, particularly for those with FH deficiency, but also for patients with other diseases associated with alternative pathway activation.